Optimalisasi Maharah Al-Kalam Bahasa Arab Melalui Media Roleplay pada Mahasiswa PBA UNM - Raudatussolihah, Baiq; Kholida, Masita Taufiqi; Laila, Hikmatul; Randy, Randy; Fathurrahman, Ali (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2025)
Abstract: This study aims to optimize the Arabic speaking skills of students of the Arabic Language Education Study Program, Makassar State University through the application of roleplay media. Speaking ability is one of the productive skills that requires intensive practice, a communicative atmosphere, and contextual learning media. This research method uses a descriptive quantitative approach with a quasi-experimental design model. The results of the study indicate that the use of roleplay media can increase students' activeness, courage, and fluency in speaking Arabic. These findings indicate that roleplay-based learning is effective in learning Arabic speaking skills because it provides a real and interactive communicative experience.